2016
DOI: 10.1080/15476286.2016.1152439
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs, the cutting edge of histone messages

Abstract: In metazoan the 3′-end processing of histone mRNAs is a conserved process involving the concerted action of many protein factors and the non-coding U7 snRNA. Recently, we identified that the processing of histone pre-mRNAs is promoted by an additional ncRNA, the Y3-derived Y3** RNA. U7 modulates the association of the U7 snRNP whereas Y3** promotes recruitment of CPSF (cleavage and polyadenylation specific factor) proteins to nascent histone transcripts at histone locus bodies (HLBs) in mammals. This enhances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Nevertheless, many questions still remain about the role of ncRNAs on aberrant nuclear organization in cancer. Interestingly, it has been suggested that ncRNAs serve as scaffolds for the formation of functional protein–RNA complexes and their sequential deposition on histones (105). These aspects are important for understanding how histone synthesis is controlled in tumor cells, which are frequently characterized by an amplification of histone gene loci (106).…”
Section: Perspectives and Open Questionsmentioning
confidence: 99%
“…Nevertheless, many questions still remain about the role of ncRNAs on aberrant nuclear organization in cancer. Interestingly, it has been suggested that ncRNAs serve as scaffolds for the formation of functional protein–RNA complexes and their sequential deposition on histones (105). These aspects are important for understanding how histone synthesis is controlled in tumor cells, which are frequently characterized by an amplification of histone gene loci (106).…”
Section: Perspectives and Open Questionsmentioning
confidence: 99%